The Lateran Church in Rome and the Ark of the Covenant : housing the Holy Relics of Jerusalem : with an edition and translation of the Descriptio lateranensis ecclesiae (BAV Reg. Lat. 712) /: housing the Holy Relics of Jerusalem : with an edition and translation of the Descriptio lateranensis ecclesiae (BAV Reg. Lat. 712). (2019) - Oftestad, Eivor Andersen
No abstract available